2024
DOI: 10.1037/aca0000453
|View full text |Cite
|
Sign up to set email alerts
|

Constructing the associations between creative role identity, creative self-efficacy, and teaching for creativity for primary and secondary teachers.

Abstract: This study explored and demonstrated the significant association between teachers' creative self-concepts, namely creative role identity and creative self-efficacy, and teaching for creativity. Multigroup structural equation modeling was used with data from 1,043 primary and secondary teachers. The results confirmed that teachers' creative role identity consisted of their self-view of creative behavior and perceived expectations from school, colleagues, and students. Both personal and contextual aspects of cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 111 publications
(182 reference statements)
1
12
0
Order By: Relevance
“…Based on the findings (model 2), CSA played a mediator role in the subscales of LI (i.e., learning self-efficacy, burnout, resilience, attitudes toward learning, openness to change, classroom affectivity, and coping). The result is supported by the findings of Huang (2022) as well as Gorjinpour and Barzegar (2022). They concluded that self-assessment is pivotal in individuals' selfefficacy and self-concept.…”
Section: Discussionsupporting
confidence: 75%
“…Based on the findings (model 2), CSA played a mediator role in the subscales of LI (i.e., learning self-efficacy, burnout, resilience, attitudes toward learning, openness to change, classroom affectivity, and coping). The result is supported by the findings of Huang (2022) as well as Gorjinpour and Barzegar (2022). They concluded that self-assessment is pivotal in individuals' selfefficacy and self-concept.…”
Section: Discussionsupporting
confidence: 75%
“…Elementary school teachers need high self-confidence to integrate creativity into the curriculum and activities during teaching and learning (X. Huang, 2022;Roebianto, 2020). The self-confidence that creativity is an important aspect that needs to be developed will lead teachers to form creative students.…”
Section: Discussionmentioning
confidence: 99%
“…While research evidence remains scarce as to how teachers’ inclusive role identity influences teachers’ inclusive teaching behaviour, identity theory postulates inherent connections between them [ 25 , 44 ]. Identity theory mentions that individuals are motivated to maintain consistency between their identity meaning and behaviour [ 28 , 45 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teachers’ inclusive role identity (TIRI) and efficacy for inclusive practice (TEIP) were examined as two teacher-level factors that mediated the PTL effects on TITB. On the one hand, identity theory [ 23 , 24 ] emphasises that the way teachers perceive and define themselves within their professional roles, as well as their interactions with significant others, has a profound influence on their beliefs and actions related to daily teaching behaviours [ 25 ]. On the other hand, teacher efficacy, as informed by social cognitive theory [ 26 ], has been consistently identified as a crucial mechanism through which the influences of PTL are transmitted and impact teachers’ instructional practices.…”
Section: Introductionmentioning
confidence: 99%